1999
DOI: 10.2337/diabetes.48.1.150
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characteristics of type 2 diabetes with and without GAD antibodies.

Abstract: The aim of the study was 1) to establish the prevalence of GAD antibodies (GADab) in a population-based study of type 2 diabetes in western Finland, 2) to genetically and phenotypically characterize this subgroup, and 3) to provide a definition for latent autoimmune diabetes in adults (LADA). The prevalence of GADab was 9.3% among 1,122 type 2 diabetic patients, 3.6% among 558 impaired glucose tolerance (IGT) subjects, and 4.4% among 383 nondiabetic control subjects. Islet antigen 2 antibodies (IA2ab) or islet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

51
423
13
18

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 449 publications
(507 citation statements)
references
References 18 publications
51
423
13
18
Order By: Relevance
“…Among subjects enrolled in the DPT-1 intervention trials, the presence of IGT results in an approximately 70% 5-year risk of type 1 diabetes, as determined from life-table analysis [11]. A similar high risk is seen among people with IGT and at risk for type 2 diabetes, with about 6% annual progression [27,28]. It is possible that many of the DQA1*0102/ DQB1*0602 subjects with abnormal glucose tolerance will either never manifest overt diabetes, or will develop diabetes only later in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among subjects enrolled in the DPT-1 intervention trials, the presence of IGT results in an approximately 70% 5-year risk of type 1 diabetes, as determined from life-table analysis [11]. A similar high risk is seen among people with IGT and at risk for type 2 diabetes, with about 6% annual progression [27,28]. It is possible that many of the DQA1*0102/ DQB1*0602 subjects with abnormal glucose tolerance will either never manifest overt diabetes, or will develop diabetes only later in life.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a slow progression of disease may result in patients being clinically classified as having type 2 diabetes or latent autoimmune diabetes of adults (LADA) [33]. In this regard, it is important to note that DQB1*0602 may not protect subjects from LADA, as one report has shown that these patients have the same frequency of this allele as seen in the general population [27]. Others report no differences in the frequency of highrisk alleles between LADA and older, but more typical type 1 patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…the presence of GAD antibodies in a patient with age at onset of diabetes of >30 years (or 35 years, as we previously proposed), and insulin independence for at least 6 months after diagnosis. Clearly, each of these cut-off values is arbitrary, and the definition of GAD antibody positivity will influence not only the prevalence but also the phenotype of LADA [6]. As Gale points out, GAD antibodies are continuously distributed throughout the population, but this applies to most autoantibodies [7], as described as early as 1963 [8].…”
mentioning
confidence: 99%
“…Among the key issues will be the demonstration that LADA has genetic features in common with both type 1 and type 2 diabetes; this information is now partially available. Patients with LADA have more type 1 high-risk HLA-DQ genotypes than patients with type 2 diabetes, but fewer than those with type 1 diabetes [6,12] and, notably, more protective HLA genotypes than patients with type 1 diabetes [6]. However, still lacking is knowledge on whether patients with LADA have the same frequency of the few type 2 diabetes susceptibility genes that have reproducibly been associated with type 2 diabetes, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation